MEMANDIRIKAN PEREMPUAN MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) - Atik Rahmawati (LITERASI: Indonesian Journal of Humanities, 2014)
UU no. 40 of 2007 on Limited Liability Companies, requires each company to implement Corporate Social Responsibility (CSR) program. This encourages PT. Earth Suksesindo forms a special division that manages the social fund company in a department called the Department of Community Relations and Development Department. The formation of this department indicates the seriousness of the company in the management of the program while ensuring that CSR can be executed and useful for the development of social, economic, and environmental. One of the activities that has managed a positive impact on improving the local economy is the empowerment of women by forming groups of oyster mushroom cultivation. This program puts women initially limited to managing household finances into productive workers who are able to contribute an income to the economic improvement of families. Keywords: corporate social responsibility, empowerment of women, oyster mushroom cultivation